2014
DOI: 10.1016/j.envsci.2014.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Scientific collectives in region-building processes

Abstract: During the last 30 years, growing demand for science-based policy making has contributed to the mobilization of scientific cooperation alongside transnational political arrangements for addressing environmental issues. Following the contemporary trend towards regionalizing environmental policy and practice, many of these scientific joint efforts have focused on a regional scale. This article examines regional scientific cooperation in the context of the institutionalization of mountain regions in Europe. Such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…For example, it was suggested to establish a knowledge platform or platforms with a particular focus on cities. These are envisioned to be accessible and open for knowledge gathering, aggregating, and cocreating as a NbS stewardship community (Bodin and Crona 2009, Crona and Hubacek 2010, Fisher et al 2012) that adheres to the principles of knowledge sharing (Connolly et al 2013, Debarbieux et al 2014) and generative learning (Richter et al 2015). In conjunction with the NbS stewardship community, the second proposal for knowledge valorization includes the empowerment of NbS ambassadors to promote NbS and engage in a science-community advocacy for NbS by making NbS benefits and risks communicable to citizens and politicians alike.…”
Section: Opportunities Facilitating Action For Nbsmentioning
confidence: 99%
“…For example, it was suggested to establish a knowledge platform or platforms with a particular focus on cities. These are envisioned to be accessible and open for knowledge gathering, aggregating, and cocreating as a NbS stewardship community (Bodin and Crona 2009, Crona and Hubacek 2010, Fisher et al 2012) that adheres to the principles of knowledge sharing (Connolly et al 2013, Debarbieux et al 2014) and generative learning (Richter et al 2015). In conjunction with the NbS stewardship community, the second proposal for knowledge valorization includes the empowerment of NbS ambassadors to promote NbS and engage in a science-community advocacy for NbS by making NbS benefits and risks communicable to citizens and politicians alike.…”
Section: Opportunities Facilitating Action For Nbsmentioning
confidence: 99%
“…The first of these can be widened to include the characterisation of mountains with regard to biophysical and even socio-economic criteria. As can be seen from the process of generating and maintaining attention to mountain issues described above, a third argument is as a basis for advocacy, policy-making or collective action (Rudaz 2009;Debarbieux et al 2014). With this background, this paper has two aims.…”
Section: Introductionmentioning
confidence: 99%
“…Individual scientists have played essential roles in creating and defining our understandings of the world's mountains (Debarbieux and Rudaz, 2015) and have also provided descriptions and analyses of the development and implementation of transnational governance processes in mountain areas, of which many are cited above. As Debarbieux et al (2014) have also shown, 'scientific collectives' have also contributed to the development and implementation of such processes for the mountains of Europe and Central Asia -and also have the potential, sometimes partly realized, to monitor the extent to which they achieve their goals. As they note, the Science for the Carpathians Initiative emerged with support from the European part of the global Mountain Research Initiative (MRI), which has also supported the development of networks of scientists in Africa, Latin America, and Southeast Europe, as well as globally (Greenwood, 2013).…”
Section: Agency: Nonstate Actors -Individuals To Organizationsmentioning
confidence: 95%